Pemberdayaan Kelompok Tani Dalam Pemanfaatan Limbah Pertanian Menjadi Pupuk Organik Di Desa Selobanteng, Kecamatan Banyuglugur, Kabupaten Situbondo - Utomo, Budi; Tanjungsari, Ardina; Muhammad, Nur; Respati, Adib Norma; Subagja, Hariadi; Yuniati, Erna (ABHIPRAYA: Jurnal Pengabdian Masyarakat Kesehatan dan Sains, 2023)
The application of Liquid Organic Fertilizer (LOF) has been widely used and is increasingly popular among people plant lover and farmer. LOF materials are easy to find and use more efficiently. The implementation of empowering the Selobanteng Farmers Group in making POC is an effort to utilize the potential of the surrounding environment in the form of agricultural waste (waste originating from farmers and breeders). This activity was carried out in Selobanteng Village, Banyuglugur District, Situbondo Regency. The method used in this activity is providing material and practice. The material delivered is the difference in liquid and solid organic fertilizer, also various kinds of solid organic fertilizer.Practice making POC using 5 liters of cow urine, 5 liters of rabbit urine, 125 ml molasses and 1.5 ml kefir whey. Making POC provides benefits, namely increasing residents' knowledge about the benefits of agricultural waste materials, increasing awareness of environmental health and providing economic value for residents, because it reduces spending on purchasing fertilizer for farmers and can increase income from sales.